Penanaman Sikap Mitigasi Kebakaran Siswa SD Joseph Khatulistiwa Sintang Dengan Permainan “Gamikar” - Nelly Wedyawati; Antonius Edy Setyawan (Prodi PGSD FIP UNM, 2020)
Sintang Region is an area of level II in the Kalimantan Barat (West Borneo). The wide area of the land are 21.635km2, most the area are forest and soil. Sintang Region Fire Department was stated that fire disaster, including soil, forest and settlement fire always became similar problem every year, especially at dry season. On the year 2015, fire was the huge disaster that happened in Sintang Region. Fire Department already tried hard to prevent that fire disaster. Socialization and Education already done by Fire Department but that was not effective and efficient. Sintang Region is an area of level II in the Kalimantan Barat (West Borneo). The wide area of the land are 21.635km2, most the area are forest and soil. Sintang Region Fire Department was stated that fire disaster, including soil, forest and settlement fire always became similar problem every year, especially at dry season. On the year 2015, fire was the huge disaster that happened in Sintang Region. Fire Department already tried hard to prevent that fire disaster. Socialization and Education already done by Fire Department but that was not effective and efficient. SD Joseph Khatulistiwa in Sintang is one of the elementary schools that has never received material on fire mitigation. For this reason, the writer needs to take up the theme of this activity by choosing SD Joseph Khatulistiwa Sintang as a target partner for Community Service activities (PkM). The method used in this PkM is learning activities through games called Gamikar. The approved activities will be carried out for 2 days. The target output of this activity is an improvement in the students' understanding of disaster mitigation. There were improvements seen from the initial and final measurements of PkM activities.